The refugee dilemma and migrant crisis: "Charity begins at Home" or "Being Home to the Homeless"? The paradoxical stance in pastoral caregiving and the infiltration and perichoresis of compassion - Louw, D. J. (HTS teologiese studies, 2016)
The current refugee and migrant crisis is revealing on a deeper ‘spiritual level’ a crisis of meaning and habitus (attitudinal crisis). Because of prejudice, xenophobia reveals a crisis of compassion and diaconic outreach. How should local communities and communities of faith display hospitality (xenophilia) to the other (stranger, foreigner, outsider) in cases where one’s own life is threatened by those you are supposed to care for? Is it true that charity begins at home, or is charity, as determined by the Christian notions of ḥesed and oiktirmos, an inclusive concept that should or could start with the homeless, the outcast and the outsider as well? This question points to the danger of selective compassion. It is argued that pastoral caregiving, within the refugee and migrant dilemma, should apply a hermeneutics of complexity and paradox. In this regard the theological paradox of the passion (pathē) of Christ should be implied in order to make room (perichoresis) for displaced and homeless people. The theological argument is based on the following presupposition: the passio dei defines ‘practice’ in pastoral theology as compassionate hospitality, as a mode of being-with, that eventually should infiltrate and penetrate the systemic paranoia of prejudice, as well as the networking dynamics of human relationships, irrespective of race, class and gender distinctions.